Lewandowski & Lutz Syndrome: A Rare Case Entity - Rikta Mohan; P Gahalaut; HS Soodan; N Mishra; MN Rastogi (Nepal Journal of Dermatology, Venereology & Leprology)
Epidermodysplasia verruciformis (EV), first described in 1922 by Lewandowski and Lutz, is a rare inherited genetic disease. The disease usually manifests in childhood with highly polymorphic, widespread lesions.